Erythroderma: A clinical and etiological study of 92 patients - Niema Aqil (Our Dermatology Online, 2019)
Background: Ery throderma is a rare and severe dermatological manifestation of a variety of diseases. It is usually difficult to find the underlying cause. This is a dermatological emergency that can be life-threatening. Objective: study aimed to examine the causes, as well as the clinical and laboratory profiles of patients with erythroderma in our department. Methods: This retrospective study was carried out in the Department of Dermatology of CHU Hassan II of Fez. Between January 2013 and May 2017. We included all patients hospitalized for acute or chronic erythroderma Results: During the study period, 1700 patients were hospitalized in the Department of Dermatology. Erythroderma was diagnosed in 92 patients (5.41%), corresponding to an incidence of 20 cases/year. The average age was 49.6 years with a male to female ratio of 0.70. The average duration of evolution was 259 days. Erythroderma was dry in 82.6% of cases. Inflammatory anemia was found in 10.9% of patients. Eosinophilia in 44.6% of patients. Hepatic cytolysis and hyponatremia in 12.9%. Kidney failure in 18.3%. The most common cause of erythroderma was exacerbation of pre-existing dermatoses (43.5%), including psoriasis (27.2%), eczema (7.6%), pemphigus foliaceous (6.5%) and pityriasis rubra pilaris (2.2%). Followed by drug reactions (38%) dominated by the drug reaction with eosinophilia and systemic symptoms syndrome (30.4%). Cutaneous T-cell lymphomas constituted 15.2% of the causes of erythroderma. The evolution was good in 87% of the patients, whose methods of management were based on symptomatic measures in association with the etiological treatment. Conclusion: Erythroderma is a severe dermatological syndrome of various etiologies. Drug inducederythroderma is a very important entity to know. Indeed, its early diagnosis allows a fast and adequate care thus improving the prognosis of this entity.